Sólidos arquimedianos: uma abordagem construtiva e investigativa em oficina presencial e uma exploração de classes de sólidos via software Poly em oficina remota com uma proposta de uso no ensino médio - Freitas, Patrícia Barcelos de Oliveira (2020)
This dissertation is based on the study of teaching spatial geometry in which it represents various situations in our three-dimensional world. Many people have difficulties in dealing with the flat figure drawn on a flat book and therefore the difficulty in understanding it and relating it to the concrete three-dimensional object. Thinking in this context, we present in this work a study on the Platonic (regular and convex) and Archimedean (semi-regular) solids obtained by truncation, snubification and expansion. With that, we recall the concepts of the number of edges, faces and vertices, and the relationship of Euler between the number of its elements V - A + F = 2 . Complementing the study, we show a brief tutorial on the Poly software, an assistant in online class and report the experiences of a class of the 2nd year of high school in the construction of these solids. We had testimonials from students who, through the concrete handling of solids and the use of Poly, started to find them beautiful, colorful and which facilitated their learning. Thus it was concluded that the Archimedean solids can be recovered and used as an object that facilitates the teaching and learning of Geometry.